Development of Interactive Learning Media (Scaffolding) on Learning Materials of Stone and Concrete - Novianto Adi Nugroho; Rosihan Ari Yuana; Taufiq Lilo Adi Sucipto (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2019)
This research aims to develop interactive learning media on learning materials of stone and concrete for building engineering majors in class X and knowing the feasibility based on material experts, media experts and learning practitioners assessment’s and to know the usability level of its so it can be applied on teaching and learning activities. Research methods that used in this research is research and development method’s modified with 4-D development models. These method includes 4 development phase’s namely, (1) Defining phase (Define), (2) Designing phase (Design), (3) Developing phase (Develop), (4) Disseminating phase (Disseminate). Results of the research showed that interactive learning media (scaffolding) has been successfully created with 94% of feasibility level’s, its consisting of 90,5% of material feasibilities from material expert, 92% of media feasibilities from media expert and 99,5% of learning feasibilities from learning practitioners. So, it can be concluded that interactive learning media (scaffolding) has a very feasible of feasibility levels. Results of the research also showed that interactive learning media (scaffolding) has 86% of usability levels that consisted of 88,5% of effectively component’s, 87,5% of efficiency component’s and 81% of user satisfaction component’s. So, it can be concludes that interactive learning media (scaffolding) has a very good usability levels to use by media user’s.